2013
DOI: 10.1115/1.4023549
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fuel Temperature on Injection Process and Combustion of Dimethyl Ether Engine

Abstract: To investigate the effects of fuel temperature on the injection process in the fuel-injection pipe and the combustion characteristics of compression ignition (CI) engine, tests on a four stroke, direct injection dimethyl ether (DME) engine were conducted. Experimental results show that as the fuel temperature increases from 20 to 40 °C, the sound speed is decreased by 12.2%, the peak line pressure at pump and nozzle sides are decreased by 7.2% and 5.6%, respectively. Meanwhile, the injection timing is retarded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…As a result, the peak in-cylinder pressure is reduced during the combustion process with the increase of ethanol fuel temperature. This reduced peak pressure was also observed in compression-ignition engines fuelled with heated rapeseed methyl ester (RME) [24], dimethyl ether (DME) [32], diesel and cetane [33].…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…As a result, the peak in-cylinder pressure is reduced during the combustion process with the increase of ethanol fuel temperature. This reduced peak pressure was also observed in compression-ignition engines fuelled with heated rapeseed methyl ester (RME) [24], dimethyl ether (DME) [32], diesel and cetane [33].…”
Section: Resultsmentioning
confidence: 60%
“…When the ethanol fuel temperature is increased from 50°C to 90°C, the density of the ethanol fuel decreases from 763 to 721 kg/m 3 , viscosity decreases from 0.676 to 0.374 mPa s, and surface tension decreases from 0.0202 to 0.0152 N/m [34]. Experiments and simulations on the fuel injection process showed that, when the fuel temperature was increased, the actual injection timing was retarded, the peak rail pressure was decreased and the injection duration was prolonged [32,35]. The fuel mass flow rate was decreased with the increase of fuel temperature because of the decreased fuel density [24,36,37].…”
Section: Combustion Characteristics With Edi Heating At the Original mentioning
confidence: 99%
“…This causes a lower maximum combustion pressure and a more delayed start of combustion: both these effects lead to a reduction in the NO x emissions. 14,15 Furthermore, a reduction in the fuel temperature can cause a higher non-uniformity degree in the fuel-air mixture, which can increase the time necessary to reach a constant level of evaporation rate and can lead to augmented emissions in unburned HC. 16 A significant sensitivity of fuel economy and NO x emission level to the fuel temperature at the injector nozzle has been noticed even for a biodiesel fueled engine, especially if low EGR rate is used.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that a larger injection angle provides longer provides longer floor jets with less fuel outside the chamber, and the re-entrant chamber with a round lip and bottom corner makes the fuel distribution better. Many other investigations [8][9][10][11][12][13][14][15], such as into injection strategies, nozzle structures, fuel properties, chamber structures and in-cylinder flow fields, were carried out. In brief, these investigations focused on fuel spray, air motion, and chamber profile and their interactions.…”
Section: Introductionmentioning
confidence: 99%